PENGARUH STRATEGI PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR FISIKA DASAR I MAHASISWA STKIP TAPANULI SELATAN - SERI ASMAIDAH NASUTION (Institut Pendidikan Tapanuli Selatan, 2017)
This research was conducted using the method of experiment. The population in this study were all students of class with a total of 14 students. The sampling technique used in this research using total sampling. For data preparation techniques X and Y variables to use observation and tests. Observation is used to capture the data variable X, and the result of the acquisition of the observations done to variable X obtained an average value of 4 that is in the category of